Quality of neonatal cranial ultrasound Interpretation among doctors in the Western Cape Metro: a clinical survey - Belay, Fitsum (Division of Neonatology, 2024)
Background: Cranial ultrasound (cUS) is a recommended skill for paediatric and neonatal trainees in South Africa. Surveys in other countries showed inadequate knowledge and subsequently a global trend towards standards and training recommendations. There are no guidelines for training of clinicians performing cUS in South Africa. Objectives: To survey the following aspects of cUS among paediatric and neonatal trainees in the University of Cape Town (UCT): duration of paediatric training, experience and supervision; knowledge of reporting content, procedural and technical aspects; interpretation of common neonatal cUS pathologies and confidence in scan interpretation and counselling. Methods: An online survey was sent to all trainees, who had worked at least one month at a neonatal unit on the UCT training platform. The survey included seven questions on cUS interpretation. Procedural and image knowledge was compared between groups with ≥ 24 months' experience versus shorter duration. Results: Thirty-one paediatric registrars and five neonatal subspecialty senior registrars were sent the survey. Twenty-six surveys were returned (72%). None of the trainees had attended a formal cUS course, 18 (69%) had attended a formal lecture from a neonatologist, and 8 (30%) had attended a formal tutorial from a consultant. Ten (38%) trainees received initial training from other registrars, medical officers, or self-study. The components of a cUS report were stated as description of anatomy and haemorrhage by 24 (92%) and 21 (81%) respectively; only 17 (65%) mentioned ventricular size and other aspects of reporting were less frequently mentioned. Only 7 (27%) trainees knew the correct number of images to be taken in the coronal and sagittal planes. Correct identification of the major features of images ranged from 12% to 92% but was below 40% in five questions. Duration of training only affected answers in two questions; trainees with ≥ 24 months experience were more likely to correctly identify a normal scan (58% vs. 14%; p=0.038) and less likely to assign abnormal prognosis in a term infant with increased white matter echogenicity (0% vs. 43%; p=0.017). Conclusions: Our survey shows inadequate and variable cUS training and competency in paediatric and neonatal trainees in our institution. The findings indicate the need for a structured training program and standardised diagnostic and training criteria to accredit clinicians who perform and report on neonatal cUS.